2022
DOI: 10.3390/en15196984
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on IoT-Enabled Smart Grids: Emerging, Applications, Challenges, and Outlook

Abstract: Swift population growth and rising demand for energy in the 21st century have resulted in considerable efforts to make the electrical grid more intelligent and responsive to accommodate consumers’ needs better while enhancing the reliability and efficiency of modern power systems. Internet of Things (IoT) has appeared as one of the enabling technologies for smart energy grids by delivering abundant cutting-edge solutions in various domains, including critical infrastructures. As IoT-enabled devices continue to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 150 publications
0
26
0
1
Order By: Relevance
“…It can provide energy from different power sources, including renewables and storage [21]. Table 2 classifies and compares the widely used communication network technology in smart grid systems [22][23][24][25].…”
Section: Work Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…It can provide energy from different power sources, including renewables and storage [21]. Table 2 classifies and compares the widely used communication network technology in smart grid systems [22][23][24][25].…”
Section: Work Backgroundmentioning
confidence: 99%
“…Smart grid systems integrate renewable energy sources such as wind, solar, and storage into the grid system. These new power generation technologies are smaller, more widespread, greener, and able to maintain grid resilience and spread congestion points [1][2]. A smart grid uses an extensive sensor network supported by a two-way communication system to constantly monitor grid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The different feature of the smart grid over the traditional grid has been listed in Table 1 [6], [7], [8], [9]. It is worth mentioning that all kinds of faults have a direct effect on the power system generation, hence the smart grid has been proposed to give a good solution for the system under faults, in addition, the system has a good dynamic response under the dynamic change of the system wither was a fault or load change.…”
Section: Introductionmentioning
confidence: 99%
“…Following the spread of COVID-19, it was found that 71% of security specialists believe that security vulnerabilities in IoT networks are increasing [10,11]. Some studies [12][13][14] describe the attacks and security vulnerabilities of each IoT layer and suggest ways to protect privacy [15][16][17]. Attacks on Internet of Things devices have increased and several studies have developed intrusion detection systems [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The inertia weight is changed in the third stage using the Eq (13). The fourth stage involves updating the position and velocity parameters in the APSO-CNN using the Eqs (11) and (12). Increase the number of iterations by one in the fifth step.…”
mentioning
confidence: 99%